Strengthening Agricultural Value Chains to Improve coffee Farmers’ Economic Resilience in South Sumatera - Maya Sari; Mutata Uwi’ah (Journal of Innovative and Creativity, 2026)
This study examines how strengthening agricultural value chains can improve the economic resilience of coffee farmers in South Sumatra, Indonesia, using a qualitative case-study design. Data were collected through semi-structured interviews with smallholder farmers and key value-chain actors (village collectors, district traders, processors, cooperative leaders, and extension stakeholders), complemented by field observations and document review. Thematic analysis indicates a predominantly trader-led chain in which price formation and quality grading are concentrated downstream, limiting farmers’ bargaining power and weakening incentives for consistent quality improvement. Upgrading constraints cluster around post-harvest capacity, time and labor shortages, liquidity pressure that forces rapid sales, and uneven access to guidance and feedback. Institutions and local networks matter as practical resilience mechanisms: where farmer groups or cooperatives function well, farmers report clearer coordination, stronger learning, and more predictable market access, although compliance demands can exclude resource-constrained households. Resilience is also shaped by shock pathways along the chain; climate variability and quality losses translate quickly into income shocks when governance is opaque and service support is weak. The study proposes strengthening actions that are feasible at the farm gate: transparent and shared grading references, low-cost post-harvest upgrading support, strengthened collective marketing and governance, and better information and service linkages to reduce dependency and uncertainty. These measures can shift value-chain strengthening from isolated technical fixes toward inclusive governance improvements that stabilize income and enhance coping and recovery capacity for coffee households. Policy implications emphasize targeted extension, simple infrastructure, and fair incentives so that upgrading benefits reach vulnerable farmers directly.